PENYULUHAN PELATIHAN KADER PEMBERDAYAAN MASYARAKAT DESA - Kende, Yizreel Junus (Nindikayla Institute, 2023)
The role of Village Community Empowerment Cadres (KPMD) is very important for the continuity of village development. One of them is to assist in the preparation of development plans and facilitate participatory development planning deliberations. This training was held to increase the capacity of the Assistants as Village Community Assistance Cadres (KPMD) who drive community empowerment and communicate directly with the PNPM Task Force (Satker) Alalak sub-district office South Kalimantan Province This requires partners to understand that changes in the external environment must be balanced with adequate internal capabilities Both administrative skills and implementation of technical/communication skills with community/officials/community leaders, coordination and facilitation. This assistance is with direct counseling methods and The results of the mentoring were found that the cadres could understand their performance to develop their regions, while the conclusion of this activity was to educate the Village Community Empowerment Cadres for better village development